DEVELOPMENT OF PROFESSIONAL STANDARDS AND CERTIFICATION SYSTEM - Ilya I. Rodin (Статистика и экономика)
In article process of development of professional standards, and also systems ofcertiﬁcation and an assessment of qualiﬁcation of shots is described. Requirements of modern business in the Russian Federation to shots are described. Research of developed and introduced professional standards in separate branchesof national economy is conducted. Also interaction business of communities and executive authorities in the course of development and deployment of professionalstandards and system of certiﬁ cation of shots is described.